A food-level substitution analysis assessing the impact of replacing regular-fat dairy with lower fat dairy on saturated fat intake at a population level in Canada. Issue 5 (28th July 2021) - Harrison, Stéphanie; Brassard, Didier; Garriguet, Didier; Lemieux, Simone; Lamarche, Benoît
ABSTRACT: Background: The 2019 Canada's Food Guide recommends the consumption of lower fat dairy products to reduce saturated fat (SFA) intakes. Objectives: The objective of this study was to assess the impact of such recommendation on SFA intake at a population level in Canada. Methods: Analyses were conducted based on dietary intakes from the nationally representative 2015 Canadian Community Health Survey–Nutrition (unweighted n  = 20, 103). Dietary intake was assessed using 24-h dietary recalls. Food-based substitution modeling analyses were conducted by replacing all regular-fat dairy products reported by an equal amount of a corresponding lower fat dairy product. Regular-fat dairy products included milks ≥2% fat, cheeses >25% fat, and yogurts ≥2% fat. Corresponding lower fat replacement products were 1% fat milks, 10–25% fat cheeses, and <2% fat yogurts. The National Cancer Institute method was used to account for within-person variation in dietary intakes. Results: Replacing all regular-fat dairy products consumed by Canadians (ages ≥2 y) by a corresponding lower fat product reduced the population's SFA intake from 10.8% of total energy intake (%E; 95% CI: 10.7%, 11.0%) to 10.0%E (95% CI: 9.8%, 10.2%). This reduction was mostly attributable to the milk and cheese substitutions (mean SFA reductions of −0.3%E each). The proportion of the population with an SFA intake <10%E was 34.7% (95% CI: 31.2%, 38.2%) before substitution and 51.5% (95% CI: 47.5%, 55.5%) after substitution. Conclusions: This food-based substitution modeling analysis suggests that SFA intakes at a population level are slightly reduced if all regular-fat dairy products consumed by Canadians were replaced by a lower fat dairy product. Approximately half of the population would still consume SFAs in excess of 10%E even if all regular-fat dairy consumed were replaced by lower fat dairy.